2000
DOI: 10.2134/agronj2000.925875x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chlorophyll Meter Sufficiency Indices for Nitrogen Management of Irrigated Rice in Asia

Abstract: Low N fertilizer recovery efficiency (RE) remains a problem in rice (Oryza sativa L.) production in Asia. The chlorophyll meter has been shown to identify when rice is in need of a N top‐dressing, that if applied would result in greater agronomic efficiency (AE) of N fertilizer than commonly practiced, pre‐set timing schemes. Critical chlorophyll meter readings have been used to match N top‐dressing with plant demand for the cultivar IR72, but fixed critical readings may not apply to multiple cultivars and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Chlorophyll fluorescence emission was measured from the adaxial surface of second-fully expanded leaf at the vegetative stage or flag leaf at the reproductive stage using a fluorescence monitoring system (model FMS 2; Hansatech Instruments Ltd., Norfolk, United Kingdom) according to Loggini et al (1999) and Maxwell and Johnson (2000) . Leaf greenness was measured using SPAD (SPAD-520Plus, Konica Minolta, Osaka Japan) at the same leaf position ( Hussain et al, 2000 ). LBS was visually scored on a scale of 1 (no symptom on leaf) to 9 (dead leaf) according to the IRRI Standard Evaluation System for rice ( SES, 2013 ; Supplementary Figure S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chlorophyll fluorescence emission was measured from the adaxial surface of second-fully expanded leaf at the vegetative stage or flag leaf at the reproductive stage using a fluorescence monitoring system (model FMS 2; Hansatech Instruments Ltd., Norfolk, United Kingdom) according to Loggini et al (1999) and Maxwell and Johnson (2000) . Leaf greenness was measured using SPAD (SPAD-520Plus, Konica Minolta, Osaka Japan) at the same leaf position ( Hussain et al, 2000 ). LBS was visually scored on a scale of 1 (no symptom on leaf) to 9 (dead leaf) according to the IRRI Standard Evaluation System for rice ( SES, 2013 ; Supplementary Figure S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly important for N, as the losses are relatively high but can only be reduced with higher labour requirements. Leaf-colour charts or chlorophyll meters are helpful in this, as it can determine the time and rate at which N fertiliser application is required to maximise the use efficiency, based on the depletion of leaf greenness (Hussain et al, 2000;Singh et al, 2002;Alam et al, 2005;Gupta & Seth, 2007;Nhamo et al, 2014). Experiments conducted in the Philippines revealed that the N fertiliser rate could be reduced by 30-45% without affecting the grain yield of rice when N is applied based on the leaf colour chart compared with the conventional practice (Hussain et al, 2000).…”
Section: In-season Nutrient Managementmentioning
confidence: 99%
“…Leaf-colour charts or chlorophyll meters are helpful in this, as it can determine the time and rate at which N fertiliser application is required to maximise the use efficiency, based on the depletion of leaf greenness (Hussain et al, 2000;Singh et al, 2002;Alam et al, 2005;Gupta & Seth, 2007;Nhamo et al, 2014). Experiments conducted in the Philippines revealed that the N fertiliser rate could be reduced by 30-45% without affecting the grain yield of rice when N is applied based on the leaf colour chart compared with the conventional practice (Hussain et al, 2000). In Bangladesh, N application based on the leaf colour chart increased the grain yield by 0.1-0.7 t ha −1 compared with farmer's management (Alam et al, 2005).…”
Section: In-season Nutrient Managementmentioning
confidence: 99%
“…However, different factors may affect the relative chlorophyll index measurements performed by these devices (Silveira & Gonzaga 2017). Therefore, the nitrogen sufficiency index (NSI) has been used with the purpose of isolating the effect of the N concentration in the leaves from other factors that may influence the readings (Hussain et al 2000).…”
Section: Introductionmentioning
confidence: 99%